Pengaruh Self Regulated Learning dan Self Efficacy Terhadap Academic Burnout Mahasiswa Pendidikan Ekonomi Universitas Siliwangi - Ulfi Tiya Fauziyah; Ai Nur Solihat; Kurniawan Kurniawan (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Students have the same academic burden and demands but with different pressures and expectations, especially when they have to face the situation and conditions of the transfer of theaching and learning mobility that causes students to experience the learning saturation of the reaserch aims to find out the level of burnout academic experienced by students and the extent to which self regulated learning and self efficacy affects this. This research was conducted on Economic Education Students at Siliwangi University class of 2019, 2020 and 2021 both partially and simultaneously. This research uses a quantitative survey research method with an explanatory survey research design. The population in this research is economics education students at Siliwangi University class of 2019, 2020 and 2021. The sampling technique used is nonprobability sampling, namely saturated sampling with a total of 282 respondents. The data collection technique uses a questionnaire and the data analysis technique used is multiple limear regression analysis. The research results show that 1) self regulated learning has a significant effect on academic burnout with a significance value of 0.003 2) self efficacy has a significant effect on academic burnout with a significance value of 0.015 3) self regulated learning and self efficacy have a significant effect on academic burnout with a significance value of 0.001.